Cooperative and supportive DNA of the Universidad Cooperativa de Colombia: roots of institutional identity - Vizcaíno G., Milcíades (Cooperativismo & Desarrollo, 2017)
Purpose: The central question that this article proposes to answer is what identity has the Universidad Cooperativa de Colombia forged and what continuities and discontinuities does it present throughout its operation? Since the University, like all of its kind, is a complex organization that has multiple dimensions derived from its mission, it is not possible to take them all into account.Description: This succinct presentation focuses only on institutional identity, which traverses the University’s historical trajectory.Point of view: It is interesting to clarify if the history of the Universidad Cooperativa de Colombia has been a testimony of fidelity to its roots, origin of its identity, and if its mottos of "A university, a whole country" and "Sailing together", express its vocation and destiny, born of the intentionality of its founders.Conclusions: Traces of institutional identity are explored with a useful analytical framework to historically review the conformation and role of Indesco, the Institute of Social Economy and Cooperativism, that later became Indesco University and later on, a University.
Keywords: Indesco; institutional identity; trajectory; Universidad Cooperativa de Colombia